Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(x^2+12x+35\)
\(=x^2+5x+7x+35\)
\(=\left(x^2+5x\right)+\left(7x+35\right)\)
\(=x\left(x+5\right)+7\left(x+5\right)\)
\(=\left(x+5\right)\left(x+7\right)\)
b)\(x^2-x-56\)
\(=x^2+7x-8x-56\)
\(=\left(x^2+7x\right)-\left(8x+56\right)\)
\(=x\left(x+7\right)-8\left(x+7\right)\)
\(=\left(x+7\right)\left(x-8\right)\)
c)\(5x^2-x-4\)
\(=5x^2-5x+4x-4\)
\(=\left(5x^2-5x\right)+\left(4x-4\right)\)
\(=5x\left(x-1\right)+4\left(x-1\right)\)
\(=\left(x-1\right)\left(5x+4\right)\)
TL:
a)\(x^2+5x+7x+35\)
=\(x\left(x+5\right)+7\left(x+5\right)\)
=\(\left(x+7\right)\left(x+5\right)\)
b) \(x^2-x-56\)
=\(x^2+7x-8x-56\)
=\(x\left(x+7\right)-8\left(x+7\right)\)
=\(\left(x-8\right)\left(x+7\right)\)
d)\(4x^4+1=\left(2x^2\right)^2+4x^2+1-4x^2\)
=\(\left(2x^2+1\right)^2-4x^2\)
=\(\left(2x^2+1+4x\right)\left(2x^2+1-4x\right)\)
.......................(tự lm)
hc tốt
a)x^2-(a+b)x+ab
= x^2 - ax - bx + ab
= (x^2 - ax) - (bx - ab)
= x(x-a) - b(x-a)
= (x-b)(x-a)
b)7x^3-3xyz-21x^2+9z
=
c)4x+4y-x^2(x+y)
= 4(x + y) - x^2(x+y)
= (4-x^2) (x+y)
= (2-x)(2+x)(x+y)
d) y^2+y-x^2+x
= (y^2 - x^2) + (x+y)
= (y-x)(y+x)+ (x+y)
= (y-x+1) (x+y)
e)4x^2-2x-y^2-y
= [(2x)^2 - y^2] - (2x +y)
= (2x-y)(2x+y) - (2x+y)
= (2x -y -1)(2x+y)
f)9x^2-25y^2-6x+10y
=
a, x^2 + 5x +4
= x^2 + 1x + 4x + 4
= (x^2 + 1x) + (4x + 4)
= x ( x + 1 ) + 4 ( x + 1 )
= (x + 1) (x + 4)
b, x^2 - 6x + 5
= x^2 - 1x - 5x + 5
= (x^2 - 1x) - (5x - 5)
= x (x - 1) - 5 (x - 1)
= (x - 1) (x - 5)
c, x^2 + 7x + 12
= x^2 + 3x + 4x + 12
= (x^2 + 3x) + (4x + 12)
= x (x + 3) + 4 (x + 3)
= (x + 3) (x + 4)
d, 2x^2 - 5x + 3
= 2^x2 - 2x - 3x + 3
= 2x (x - 1) - 3 (x - 1)
= (x-1) (2x - 3)
e, 7x - 3x^2 - 4
= 3x + 4x - 3x^2 - 4
= (3x - 3x^2) + (4x - 4)
= 3x (1 - x) + 4 (x - 1)
= 3x (1-x) - 4 (1 - x)
= (1 - x) (3x - 4)
f, x^2 - 10x + 16
= x^2 - 2x - 8x + 16
= (x^2 - 2x) - (8x - 16)
= x (x - 2) - 8 (x - 2)
= (x - 2) (x - 8)
a, (x+1)(x+4)
b,(x-5)(x-1)
c,(x+3)(x+4)
d,(2x-3)(x-1)
e,(-3x+4)(x-1)
f, (x-8)(x-2)
a)\(3x^2-8x+4\)
\(=3x^2-2x-6x+4\)
\(=x\left(3x-2\right)-2\left(3x-2\right)\)
\(=\left(x-2\right)\left(3x-2\right)\)
b)\(4x^4+81\)
\(=4x^4+36x^2+81-36x^2\)
\(=\left(2x^2+9\right)^2-36x^2\)
\(=\left(2x^2-6x+9\right)\left(2x^2+6x+9\right)\)
c)\(x^8+98x^4+1\)
\(=\left(x^8+2x^4+1\right)+96x^4\)
\(=\left(x^4+1\right)^2+16x^2\left(x^4+1\right)+64x^4-16x^2\left(x^4+1\right)+32x^4\)
\(=\left(x^4+8x^2+1\right)^2-16x^2\left(x^4-2x^2+1\right)\)
\(=\left(x^4+8x^2+1\right)^2-16x^2\left(x^4-2x^2+1\right)\)
\(=\left(x^4+8x^2+1\right)^2-\left(4x^3-4x\right)^2\)
\(=\left(x^4+4x^3+8x^2-4x+1\right)\left(x^4-4x^3+8x^2+4x+1\right)\)
d)\(x^4+6x^3+7x^2-6x+1\)
\(=x^4+3x^3-x^2+3x^3+9x^2-3x-x^2-3x+1\)
\(=x^2\left(x^2+3x-1\right)+3x\left(x^2+3x-1\right)-\left(x^2+3x-1\right)\)
\(=\left(x^2+3x-1\right)\left(x^2+3x-1\right)\)\(=\left(x^2+3x-1\right)^2\)
a)
\(x^4+4=(x^2)^2+2^2+2.x^2.2-4x^2\)
\(=(x^2+2)^2-(2x)^2=(x^2+2-2x)(x^2+2+2x)\)
b)
\(64x^4+81=(8x^2)^2+9^2+2.8x^2.9-144x^2\)
\(=(8x^2+9)^2-(12x)^2=(8x^2+9-12x)(8x^2+9+12x)\)
c)
\(x^8+4=(x^4)^2+2^2+2.x^4.2-4x^4\)
\(=(x^4+2)^2-(2x^2)^2=(x^4+2-2x^2)(x^4+2+2x^2)\)
d)
\(x^4+18x^2=(x^2)^2+18^2+2.x^2.18-36x^2\)
\(=(x^2+18)^2-(6x)^2=(x^2+18-6x)(x^2+18+6x)\)
e)
\(x^4+3x^2+4=(x^2)^2+2^2+2.x^2.2-x^2\)
\(=(x^2+2)^2-x^2=(x^2+2-x)(x^2+2+x)\)
f)
\(x^4-7x^2+1=(x^4-2x^2+1)-9x^2\)
\(=(x^2-1)^2-(3x)^2=(x^2-1-3x)(x^2-1+3x)\)